Performance of portable emergency suction devices in pre-hospital conditions: a pilot study in the fire brigade - Dudziński, Łukasz; Kubiak, Tomasz; Feltynowski, Mariusz; Panczyk, Mariusz; Leszczyński, Piotr (Folia Medica Cracoviensia, 2023)
Aim: Assessment of the effectiveness and efficiency of three mobile (portable) rescue aspirators models in the opinion of state fire service officers. Comparison with the use of the medical simulation element. Material and Methods: The study was conducted in organizational units of the State Fire Service (24-hour officers). The research consisted in carrying out the task with the use of three models of mobile rescue aspirators (manual, hand-foot, battery). Each participating firefighter had the task of sucking up an equal amount of fluid (100 ml, respectively) with each model of an aspirator. The test fluid was water at room temperature in a homogeneous 1:1 mixture with sugar (increased viscosity and density, simulated real conditions). Immediately after three suction attempts (with measured suction time), each officer completed a questionnaire on the three models used. Descriptive statistics were used to characterize the variables. The following measures were calculated for the variables: mean (M) and standard deviation (SD), minimum, maximum. The following measures were calculated for categorical variables: number (n) and frequency (%). Results: 184 officers (182 M and 2 F) took part in the study, including commanders 18.43%, rescuers 65.22%, drivers 16.30%. In the study area 1,609 officers serve in the combat division as at the end of 2021. The studied group accounts for 11.43%. Age of respondents M 34.04 SD 8.24 Min 21 Max 52, length of service M 8.48, SD 7.20 Min 1, Max 25. The longest mean time of completing the task was recorded for model 2 (hand-foot) and it was 6.77 sec. Conclusions: SFS officers highly appreciated the usefulness and effectiveness of the battery-operated automatic aspirator. This assessment may contribute to the widespread introduction of such a model to rescue sets in the SFS. Time of performing the task by mode 1 was significantly longer by elderly people. People with experience with the model 1 during rescue and firefighting operations had a significantly shorter time of performing the task with the use of the model 2. According to the subjective assessment of firefighters, the most effective is model 3, which is confirmed by the suction time obtained at the work station.
Keywords: airways; medical emergency suction device; rescue and firefighting activities